Studying the effect of the developed technology on the chemical composition of yogurt made from camel milk - Dikhanbayeva, Fatima; Zhaxybayeva, Elmira; Dimitrov, Zhechko; Baiysbayeva , Meruert; Yessirkep, Gulmira; Bansal, Nidhi (Eastern-European Journal of Enterprise Technologies, 2021)
This work aimed to conduct a comparative analysis that helps to identify the effect of the developed technology on the chemical composition of drinking yogurts made from Australian and Kazakhstani dromedary camel milk. Camel milk taken from Kazakhstan and Australia has been processed into drinking yogurt and its amino, fatty acid, vitamin, and mineral content was assayed. These identifications enabled us to compare how our developed technology is suitable for both milk types. The results of determination can be interpreted as follows. The essential and non-essential amino acid content in Kazakhstani yogurt was significantly higher compared to Australian yogurt. Aspartic and Glutamic acids were not identified in Kazakhstani yogurt. As a counterpart, Lysine and Histidine were not found in Australian yogurt. The fatty acid results demonstrated that Linoleic acid in Kazakhstani yogurt was significantly higher than in Australian yogurt, and there was more Linolenic acid in Australian yogurt than in Kazakhstani yogurt. The atherogenicity index for Kazakhstani yogurt was at a low level (0.045 %) compared to Australian yogurt (1.90 %). The ratios of omega 6 and omega 3 in Kazakhstani yogurt were 16 % greater than in Australian yogurt. Thiamine level in Kazakhstani yogurt was lower compared to Australian by up to 57 %. However, Riboflavin results in both samples were identical. The Calcium, Potassium, Sodium, and Phosphorus contents in Australian yogurt are defined as 5, 34, 34, and 30 % respectively compared to Kazakhstani yogurt. Nevertheless, Magnesium (47 %) and Iron (60 %) levels were lower in Australian yogurt than in Kazakhstani yogurt. These study results could be useful as preliminary work for scientists and producers of gerodiet products, who intend to work with camel milk as a geroprotector